Save Muscle Information–Unfiltered EEG Signal Helps Distinguish Sleep Stages - Gi-Ren Liu; Caroline Lustenberger; Yu-Lun Lo; Wen-Te Liu; Yuan-Chung Sheu; Hau-Tieng Wu (Sensors, 2020)
Based on the well-established biopotential theory, we hypothesize that the high frequency spectral information, like that higher than 100Hz, of the EEG signal recorded in the off-the-shelf EEG sensor contains muscle tone information. We show that an existing automatic sleep stage annotation algorithm can be improved by taking this information into account. This result suggests that if possible, we should sample the EEG signal with a high sampling rate, and preserve as much spectral information as possible.